Pergeseran Pola Konsumsi Leisure dan Non Leisure di Kota Semarang - Dewi, Ola Ranti; Suseno, Deky Aji (Efficient: Indonesian Journal of Development Economics, 2020)
Leisure consumption groups grew by 7.88% higher than the non-leisure group which grew by 6.27% in the year 2016. Data shows indications of a shift in consumption patterns. The purpose of this study was to analyze the shift in consumption patterns of Leisure and Non Leisure households in the city of Semarang, factors that influence the shift in consumption patterns. The research data was obtained from the BPS, and the questionnaire. The method used in this study is descriptive statistical analysis, Binary Logit Regression analysis using SPSS 25, and MPC analysis. The results of this study indicate that Leisure consumption growth in 2010-2017 is higher than the growth of non-leisure consumption which shows that there has been a shift in household consumption patterns in the city of Semarang. Shifting consumption patterns are influenced significantly by income and education level. Suggestions can be given to the government and society in general to be able to optimize the shift in consumption patterns, pay more attention to socio-economic factors of household income and education level, as well as focus on developing the economy in the field of leisure consumption in order to optimize consumption growth and total regional product. Kelompok konsumsi leisure tumbuh sebesar 7,88% lebih tinggi dari kelompok non leisure yang tumbuh sebesar 6,27% pada tahun 2016. Data menunjukkan indikasi terjadinya pergeseran pola konsumsi. Tujuan penelitian ini untuk menganalisis pergeseran pola konsumsi Leisure dan Non Leisure rumah tangga kota Semarang, faktor yang mempengaruhi pergeseran pola konsumsi. Data penelitian ini diperoleh dari Badan Pusat Statistik, dan kuesioner. Metode yang digunakan dalam penelitian ini adalah analisis statistik deskriptif, analisis Regresi Logit Biner menggunakan SPSS 25, dan analisis MPC. Hasil penelitian ini menunjukkan bahwa pertumbuhan konsumsi Leisure pada tahun 2010-2017 lebih tinggi dibandingkan dengan pertumbuhan konsumsi non leisure yang menunjukkan bahwa telah terjadi pergeseran pola konsumsi rumah tangga di kota Semarang. Pergeseran pola konsumsi dipengaruhi secara signifikan oleh pendapatan dan tingkat pendidikan. Saran yang dapat diberikan kepada pemerintah dan masyarakat pada umumnya untuk dapat mengoptimalkan pergeseran pola konsumsi, lebih memperhatikan faktor sosial ekonomi pendapatan rumah tangga dan tingkat pendidikan, serta fokus dalam pengembangan perekonomian dibidang konsumsi leisure agar dapat mengoptimalkan pertumbuhan konsumsi dan PDRB.